A Study on the Existentialist Perspective to Analyze the Need for Pure Existence in Life - Zhang, Ruimeng (Transactions on Social Science, Education and Humanities Research, 2024)
Forrest Gump is a movie full of life philosophy, telling the story of Forrest Gump, a small town boy with congenitally intellectual disabilities, who just purely experiences life at his own pace, and creates legends in multiple fields. By comparing the protagonist's innate intellectual disability with his legendary life experiences, it has triggered people's contemplation of several concepts including the purity, existence, sinking, "ordinary people", and death of life from an existentialist perspective. Sequently, based on Heidegger's existentialism, thinking about the purity, being, sinking, "ordinary people" and death of life, the author draws three conclusions. The first one is primarily associated with purity pointing out that people should "live a pure life" like Gump. The second one is mainly related to existence, which concludes that being is "to be", "to become" and "to exist". The last one is about sinking, “ordinary people” and death, illustrating that if someone wants to understand the essence of life, then he must go to death initially.